Outlook on mechanical wood processing in Estonia - Vabamäe, Toomas (Finnish Forest Research Institute, 2014)
This report aims to describe the current situation of Estonian mechanical wood processing, giving separate production overviews of sawn wood, planed wood, plywood, veneer, fiberboard, particle board, wooden carpentry, wooden furniture and prefabricated wooden houses. Estonia is highly forested and the wood processing sector is an important employer. The mechanical wood processing sector has an important role in Estonian economy and in export of goods. The recent economic recession has reshaped most of the industry, forcing companies to increase efficiency and improve their position in export markets.

This report aims to describe the current situation of Estonian mechanical wood processing, giving separate production overviews of sawn wood, planed wood, plywood, veneer, fiberboard, particle board, wooden carpentry, wooden furniture and prefabricated wooden houses. Estonia is highly forested and the wood processing sector is an important employer. The mechanical wood processing sector has an important role in Estonian economy and in export of goods. The recent economic recession has reshaped most of the industry, forcing companies to increase efficiency and improve their position in export markets.
Keywords: huonekalut; kuitulevyt; lastulevyt; puunjalostus; puurakentaminen; puusepänteollisuus; sahatavara; viilu; Estonia; sawn timber; plywood; veneer; fibreboards; chipboards; carpentry industry; furniture industry; prefabricated wooden house industry; carpentry; fiberboard; furniture; particle board; planed wood; plywood; prefabricated wooden houses; sawnwood; veneer; wood processing; planed wood; wood processing